1992
DOI: 10.1016/s0886-3350(13)80391-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative inflammation following cataract extraction caused by bacterial contamination of the cleaning bath detergent

Abstract: Five of 16 patients who had uncomplicated cataract extraction with intraocular lens (IOL) implantation within a 2.5 day period experienced increased anterior segment inflammation on their first postoperative day. Four of these five patients had phacoemulsification and one a planned extracapsular cataract extraction. All had posterior chamber IOL implantation in the capsular bag. In all patients, this anterior segment inflammation cleared with topical steroids over two to three weeks with no evident residual oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 5 publications
0
35
0
1
Order By: Relevance
“…However, in the OR, the wound was found to be sealed and thus no intracameral injections were performed. TASS may occur due to abnormalities in the pH or ionic composition of irrigating saline solutions [22]. Nevertheless, BSS was only used topically.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the OR, the wound was found to be sealed and thus no intracameral injections were performed. TASS may occur due to abnormalities in the pH or ionic composition of irrigating saline solutions [22]. Nevertheless, BSS was only used topically.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Other outbreaks have been presumed to be because of defective sterilisation and/or poor operative room hygiene, 12,13 and in these cases a variety of causative organisms can be found in one outbreak. In others, the same organism is implicated in all or most cases and intraoperative contamination can be identified, for example, internal contamination of the phacoemulsification machine 14,15 or the vitrectomy apparatus; 16,17 contamination of the ultrasonic cleaning bath and detergent, 18 viscoelastic, 19 Figure 7 Diatoms.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although cases of endophthalmitis are usually isolated, clustered outbreaks have been described and exogenous sources have sometimes been identified. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In a 14-week period, at the end of 1999, there were eight cases of postphacoemulsification endophthalmitis in the Tennent Institute of Ophthalmology, Gartnavel General Hospital, Glasgow. The Tennent Institute is the tertiary referral unit for Glasgow and the West of Scotland.…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative bacteria can be found in water baths, ultrasound baths and autoclave reservoirs. This bacteria are destroyed during heat sterilization but their heat-stable bacterial wall endotoxines remain intact and can deposit on instruments (Kreisler et al, 1992) (Holland & Morck, 2007) (Andonegui et al, 2009). Another author (Hellinger et al, 2006) found sulphate, copper, zinc or silica impurities in the autoclave steam moisture.…”
Section: Maintenance Of Surgical Materialsmentioning
confidence: 99%